Effect of a functional polymer on the rheology and microstructure of sodium alginate. (1st November 2018) - Du, Lei; GhavamiNejad, Amin; Yan, Zhi-Chao; Biswas, Chandra Sekhar; Stadler, Florian J.
Highlights: Clarification of interaction of functional copolymer with sodium alginate. Demonstration of usefulness of parameter Q to characterize hydrogels. Detailed analysis of linear and nonlinear rheology. Tailorable modulus, nonlinear behavior, and functional polymer dependence. Extension of large amplitude oscillatory shear-techniques to hydrogels. Abstract: Here, we report on the effect of functional copolymer poly(N-isopropylacrylamide-co-4-vinyl-phenylboronic acid) (NIBA) on the rheology and network structure formed by sodium alginate (SA) through linear and nonlinear viscoelasticity measurements. The hydrogel moduli at pH 3 increased with increasing NIBA addition, while the yield point decreased. Furthermore, these hydrogels showed strain-softening behavior, weak G″-overshoot marking the onset of nonlinearity, and good self-healing properties after large deformation. The zero-strain nonlinearity parameter (Q0 ) was found to be more sensitive to NIBA-addition than the linear viscoelastic properties. The blends showed a clear peak in the startup test except for SA alone and the peak intensity increased with increasing NIBA-concentration. Finally, based on all data, gelation mechanism and interaction of SA and NIBA will be clarified.